A convenient cable tension estimation method simply based on local vibration measurements to fit partial mode shapes. (1st December 2022) - Chen, Chien-Chou; Wu, Wen-Hwa; Liu, Yan-Ting; Lai, Gwolong
Highlights: A tension estimation method simply with local vibration measurements is developed. It is found that the half-wavelength of each mode is actually needed in this method. Numerical analyses are conducted to provide the guidelines for sensor deployment. Experiment of a steel strand demonstrates its excellent accuracy with 1/3 coverage. Abstract: To apply the tension estimation method based on effective vibration lengths, it has been clarified that the installation of at least one sensor near the high end of a stay cable or a suspender of arch bridge is necessary for attaining good accuracy. Efforts are made in this research to release such an undesirable requirement that may greatly hinder popular applications of this method. re-examination of formulations first reveals that the half-wavelength, rather than the whole effective vibration length, of each considered mode is actually needed in the mode shape based method. Therefore, cable tension estimation simply using local vibration measurements to fit partial mode shapes is a viable alternative as long as the accuracy in determining the half-wavelengths of all the chosen modes can be ensured. Numerical analyses with the finite element models for two stay cables are then conducted to investigate the appropriate covering range of local measurements and the preferred choice of modes. Following those guidelines, the experimental results with a pre-stressed strand are further analyzed to demonstrate that excellent accuracy in tension estimation for the experimental strand with slenderness similar to a short stay cable can be achieved when 1/2 and 1/3 covering ranges are adopted. Finally, by taking vibration measurements on a real stay cable with a length of 100 m, the accuracy for the tension value estimated from 1/4 covering range is persuasively validated with a difference less than 1 % compared to that estimated from full coverage.